Risk management and its effect on welders’ health and the work environment of shipyard industries - Nugroho, Nur Yanu; Leksono, Amin Setyo; Ciptadi, Gatot; Putra, Fadillah (Edelweiss Applied Science and Technology, 2025)
This study examines the influence of risk management implementation on occupational health and the work environment in welding activities within shipyard industries. Using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, the research identifies key factors affecting the effectiveness of risk management practices. The results indicate that welders’ competency, facility availability, internal communication, and workers’ knowledge and persuasion significantly enhance risk management implementation through the development of safe and professional work behavior. In contrast, company policy and work motivation show no significant effects, implying that formal regulations have not been fully embedded in the organizational culture. The study concludes that strengthening knowledge-sharing culture and communication systems is essential to improve risk awareness and proactive safety behavior. Practically, the findings highlight the importance of integrating continuous learning, competency development, and participatory communication into occupational safety programs to achieve a sustainable and healthy work environment.